Globalización económica y transformaciones laborales: el papel de las Normas Internacionales de Trabajo - Márquez Gómez, Laura Carolina (Universidad de San Buenaventura - Cali, 2017)
Economic globalization has influenced the transformation of the labor market, through integration into the economy and promoting new jobs for society, which ultimately led to include new forms of employment contracts where labor outsourcing results, and product is, the cooperative. Topics that have been included in the International Labour Organization through its International Standards. We therefore start by defining what is meant by globalization, what impact has this on the economy and how from it have been changes or transformations in labor, reflected in the International Labour Organization. And finally will discuss the cooperative product of the change.